The Effect of Educational Intervention Using Attitude- Behavior Pattern of Health Nutrition on Labor Productivity Index - Rasoul YARAHMADI; Mohammad reza VAFA; Parvin MORIDI; Peyman YARI; Seyyede Narjes NAJIBI; Somayeh SOLEIMANI- ALYAR (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The success of each company is related to the performance and productivity of its employees. Recent ergonomic research on this case has confirmed the relation of high stress level, weight, and other risk factors with employees' health care costs and absences. The aim of this study was to introduce the economic and productivity results derived from implementing the interventions of nutrition education using the awareness promotion, attitude correction, and behavior of labors approach according to needs of work places at the selected industry. Methods: The intervention group consisted of 104 male employees who worked at the assembly line of automobile industry and received nutrition education using the active and passive methods in a one-month intervention. To measure the effect of intervention, the health indicators of blood pressure, and body mass index, as well as the awareness questionnaire were used as the pretest and posttest measures. Data analysis was conducted using paired sample T-test using the SPSS22. The economic results achieved from the intervention were expressed as the percentage of production increase or the workers' working hours. Results: Based on the research findings, nutrition education had significantly positive effect on low blood pressure (P-value= 0.000), awareness promotion (P-value= 0.004), employee attitude (P-value= 0.003), and healthy nutrition consumption (P-value= 0.037). It also had positive but not significant effect on body mass index (P-value= 0.448). Conclusion: Ergonomic interventions with awareness promotion and attitude style approach had meaningful effect on health promotion and efficiency of labor.